Distributed cooperative secondary frequency control for power system penetrated with renewable energy sources and energy storage with communication time delays - Zhang, Runfan; Ren, Xinyi; Liu, Zixuan; Bie, Zhaohong; Chen, Chen (International journal of electrical power & energy systems, 2025)
The increasing penetration of renewable energy sources in power systems presents frequency stability challenges, as power electronic-connected sources like photovoltaics and batteries inherently provide limited inertia and damping for frequency regulation. To address this issue, this paper proposes a distributed cooperative control method for secondary frequency regulation. Additionally, it achieves economic dispatch among generators and proportional power sharing among renewable energy sources. The proposed control system enables photovoltaics and battery energy storage systems to actively manage frequency in conjunction with power generators. It operates using a sparse communication network that mirrors the topology of the power network. Moreover, the cooperative control method can tolerate communication time delays while maintaining a stable frequency response. The frequency stability of the proposed control system, both with and without time delays, is assured through Lyapunov methods and eigenvalue analysis. Validation is performed on a modified IEEE 14-bus system with integrated photovoltaics and batteries, demonstrating the efficacy of the proposed secondary frequency control. •The frequency stability is enhanced with reduced fluctuations and shortened transient periods.•This frequency control relies on a sparse network with minimized costs and enhanced resilience.•Stability of the frequency control is maintained both with and without communication time delays.